ANALISIS TEORI LABELLING DAN DEKONSTRUKSI TOKOH DALAM NOVEL BULAN TERBELAH DI LANGIT AMERIKA KARYA HANUM SALSABIELA RAIS DAN RANGGA ALMAHENDRA - Devandra Eka Savitri; Elly Firdaus; Suwarsono Suwarsono (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2018)
The research focuses its attention on the role problem is the labeling theory. This theory assumes that in society as a social structure there are various deviations. Deconstruction is the ever-present waste between "Crisis" and "Literary Criticism". The formal object of this study discusses the labeling and deconstruction associated with society and religion. While the object material is a character in the novel Moon Fly in the Sky America. This study aims to expose the nickname to Muslims and justify that Islam is not a terrorist religion in the novel of the Moon Fly in America using the theory of Labeling and Deconstruction.The method used in this study is a qualitative research method with documentation techniques, because the data taken in the novel Moon Splitted in the Sky America by Hanum Salsabiela Rais and Rangga Almahendra published in 2015 with 335 pages thick. Research using this qualitative description method will dissect on the nickname and truth that can not be separated from one another.The result is that Muslims are not a bunch of terrorist members, the mosque is not a symbol of terrorist gatherings, but a place of pouring out the hearts and worship of Muslims, the truth lurked by the hatred of the WTC tragedy that the criminals are not true Muslims, and Hanum figures trying to unite Muslims and non-Muslims to unite. Keywords: Novel, Labeling, Deconstruction